Performance of the mission critical Electrical Support System (ESS) which handled communications and data transfer between the Rosetta Orbiter and its Lander Philae while en route to and at comet 67P/Churyumov-Gerasimenko. (August 2016) - McKenna-Lawlor, Susan; Rusznyak, Peter; Balaz, Jan; Schmidt, Walter; Fantinati, Cinzia; Kuechemann, Oliver; Geurts, Koen
Abstract: The Electrical Support System (ESS), which was designed and built in Ireland, handled commands transmitted from the Rosetta spacecraft to the Command and Data Management System (CDMS) aboard its Lander Philae during a ten year Cruise Phase to comet 67P/Churyumov-Gerasimenko as well as at the comet itself. The busy Cruise Phase included three Earth flybys, a fly-by of Mars and visits to two asteroids, Steins and Lutetia. Data originating at the individual Lander experiments measured while en-route to and at the comet were also handled by the ESS which received and reformatted them prior to their transmission by Rosetta to Earth. Since the success of the Lander depended on the acquisition of scientific data, the ESS was defined by the European Space Agency to be Mission Critical Hardware. The electronic design of the ESS and its method of handling communications between the spacecraft and Philae are herein presented. The nominal performance of the ESS during the Cruise Phase and in the course of subsequent surface campaigns is described and the successful fulfilment of the brief of this subsystem to retrieve unique scientific data measured by the instruments of the Philae Lander demonstrated. Highlights: The ESS Processor is a highly reliable system mounted aboard the Rosetta spacecraft. ESS wraps commands from Rosetta in a transfer frame for forwarding to Lander Philae. Data measured by the Lander experiments are received and formatted by the ESS. The ESS performance throughout the cruise phase and at the comet was always nominal.